Comparative bioefficacy of Paecilomyces fumosoroseus and Metarhizium anisopliae var. major on Crocidolomia binotalis (Lepidoptera:Pyralidae). - Hashim, Norzita; Ibrahim, Yusof
The bioefficacy of the entomopathogenic fungi Paecilomyces fumosoroseus (Wise) and Metarhizium anisopliae var major Sorokin was compared using Crocidolomia binotalis Zeller (CWW). Exposures to sprays of 20ml-1 to 2 x 10 spores ml-1 resulted in mean larval mortality ranging from 10.3 to 100.0% 12 days after treatment. At concentrations higher than 2 x 10 spores ml-1, larval mortality was recorded in excess of 80% for both entomopathogenic fungi. Most of these larvae were observed to be moribund two days after treatment. Estimates of mean effective dose ED50 computed for P.fumosoroseus was 1926 spores ml-1 with 95% fudicial limits between 700.2-4580 spores ml-1, and this was much lower than that of M. anisopliae which was 20,000 spores ml-1 with 95% fiducial limits between 9443-41530 spores ml-1. Potency of infection by P.fumosoroseus was superior as all its series of concentrations took a much shorter time to reach mean lethal time to infectivity (LT50) compared to M.anisopliae.